Analisis Jenis Artikulus Atau Kata Sandang Dalam Naskah Drama Kereta Kencana Karya Eugene Ionesco (TERJEMAHAN W.S RENDRA) - Lia Nurhasanah (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This research aims to analyze the use of articles or articles in the drama script "Kereta Kencana". Articles are an important linguistic element in Indonesian that influences the understanding and interpretation of texts. Through a linguistic analysis approach, this research examines the use of articles in the context of the drama script, including the role and function of articles. Qualitative analysis methods are used to examine the text in depth with a focus on the use and application of articles or articles in the text. It is hoped that the results of this research will provide a better understanding of the role and function of articles in the drama script "Kereta Kencana", as well as their contribution to the overall understanding of the story and the aesthetic experience of readers or viewers.